TRACER STUDY OF 2009 -2011 PNU BSE-PE MAJOR GRADUATES - Rosanna A Diana (JIPES - JOURNAL OF INDONESIAN PHYSICAL EDUCATION AND SPORT, 2015)
The Philippine Normal University (PNU), as the National Center for Teacher Education (NCTE), considers the evaluation of the impact of Teacher Education on students as one of its research priorities. Given the above-mentioned research priority of the University, this study was intended to determine if the curricular programs are being implemented appropriately at the classroom level and if there are desired effects on student achievement and employability. Further, this study looked into the some judgments about what aspects of the curriculum will be retained, enhanced or written off can be pursued if there is an evaluation process undertaken on which decisions will be based. Moreover, the experiences of those people involved in the implementation of the program will probably suffice which modifications and adjustments are appropriate. Results of the evaluation are expected to provide bases for further improving the curriculum and the success of the implementation process. This research used the following data gathering tools / procedure: ) Questionnaire developed by CHED specifically for Tracer Study research. The rating scale intended to determine the adequacy and relevance of the different course competencies of the program was included in the questionnaire. 2.) Focus Group Discussions were conducted. The scale items were consisted of program competencies resulting from the review of the course syllabi. The Tracer Survey Questionnaire was made available to the respondents through the web. The researcher tracked down and set up a directory of the graduates covered by the study. This study revealed that the Physical Education Curricular Program of the graduates BSE Physical Education of the College of Arts and Social Sciences from 2009 to 2011 is very adequate. The knowledge and skills developed during the Pre-service training are extremely relevant and useful to the performance of the tasks in their current employment.